Novel compression stockings increase tissue re-oxygenation in recovery bouts during progressive incremental exercise - Hunter, S.; James, D. C.; Mileva, K. N. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Investigations have shown equivocal benefits of wearing graduated compression garments for exercise performance (Sperlich et al 2010; Ali et al 2011; Menetrier et al 2011). New technology incorporated into compression stocking design has been developed. Therefore, the aim of the present investigation was to evaluate its effect on parameters relating to cardiorespiratory and lower limb tissue oxygenation indices during progressive incremental exercise. Method Twelve club runners participated in a 2-trial randomized protocol consisting of 5-stages (4.5min, 30s recovery) of incremental (1km/h) treadmill running (1% incline) wearing either compression stockings (STO) or commercially available (PLAC) garments under standard football socks. Standard cardiorespiratory measures (VO2, HR, [BLa-]) were taken in parallel with continuous records of tissue haemoglobin indices (THI, TOI, HbO2, HHb) from the calf and the thigh using near-infrared spectroscopy (NIRS). The final 30s of stages corresponding to steady-state, threshold and maximal exercise, along with 30s recovery after these stages were analysed and subjected to 2-way repeated measures ANOVA corrected with Holm-Sidak posthoc tests. An alpha level for statistical significance was set at 0.05. Results During exercise, cardiorespiratory and NIRS parameters showed significant change over time (p<0.05); but were not different between conditions (p>0.05). In the 30s recovery period between stages, significantly steeper changes in calf HHb and TOI were observed in STO (p<0.05) compared to PLAC, indicating faster muscle reoxygenation during recovery. No condition effects (p>0.05) were observed in thigh muscle oxygenation rates. Discussion The findings of the present study demonstrate that wearing novel compression stockings during incremental intermittent exercise enhances tissue reoxgenation during the recovery periods. This finding is in agreement with the observations of Menetrier et al. (2011) who reported increased calf tissue oxygen saturation during exercise recovery. They also support the findings of Ali et al (2011) and Sperlich et al (2010) in reporting that STO resulted in no cardiorespiratory or performance benefit during exercise. These findings merit further investigation into the effects of faster recovery tissue re-oxygenation on high intensity intermittent exercise performance.